A randomized controlled trial to evaluate the effects of high Protein Complete (lActo) VEgetaRian (PACER) diet in non-diabetic obese Asian Indians in North India. Issue 12 (December 2017) - Bhardwaj, Swati; Misra, Anoop; Gulati, Seema; Anoop, Shajith; Kamal, Vineet Kumar; Pandey, Ravindra Mohan
Abstract: In view of the increasing prevalence of obesity in largely vegetarian Asian Indians, it is important to research a high protein, low carbohydrate vegetarian diet. The present study was designed to evaluate the effects of a "High P rotein C omplete (lacto) V E geta R ian Diet (Acronym; 'PACER diet'), on weight, body composition and metabolic profiles in non-diabetic obese Asian Indians living in north India. In this 8-week randomized control trial, 102 vegetarian subjects with body mass index (BMI) >25 kg/m 2 were randomized to either a test diet (PACER diet; high protein, high fat and moderately low carbohydrate, lacto-vegetarian diet) or control diet (standard vegetarian diet formulated as the dietary guidelines for Asian Indians) after 4 weeks of diet and exercise run-in period. A standard exercise protocol was followed for both groups. Body weight, BMI, waist circumference (WC), blood pressure, fasting plasma glucose (FPG), fasting serum insulin and lipid profile were assessed before and after the intervention. There was significant weight loss along with improvements in cardio-metabolic risk factors among both the groups post intervention. Percent reductions in the intervention group for weight (6.1± 2.9; p < 0.001), WC (3.9 ± 1.7; p < 0.001), FPG (5.9 ± 3.2; p < 0.001), total cholesterol (10.2 ± 6.3: p < 0.001), serum triacylglycerol (13.6 ± 10.6; p < 0.001) and low-density lipoprotein cholesterol (11.9 ± 7.1; p < 0.001]) were significantly greater than the control diet group. In summary, intervention with a PACER diet (high protein, high fat and moderately low carbohydrate, lacto-vegetarian diet) showed significant improvement in weight loss, body composition and cardio-metabolic profile as compared to a standard vegetarian diet among obese Asian Indians in north India.